COMPARISON OF EFFECTIVENESS OF DIAPHRAGMATIC BREATHING AND PURSEDLIP EXPIRATION EXERCISES IN IMPROVING THE FORCED EXPIRATORY FLOW RATE AND CHEST EXPANSION IN PATIENTS WITH BRONCHIAL ASTHMA (International Journal of Physiotherapy, 2016)
Background: Asthma is growing problem in India and throughout the world. Breathing exercises are commonly incorporated in overall pulmonary rehabilitation program of patients with bronchial asthma. However there is a lack of awareness regarding following a specific exercise prescription which is based on individual’s requirements. Physiotherapist can help in designing an exercise prescription specific to an individual possibly to achieve more control over bronchial asthma.Methods: Thirty patients both male and female aged between 20 and 40 years diagnosed with bronchial asthma by the physician were assigned in two groups. Group-1 patients were given diaphragmatic breathing exercises and group-2 patients were given pursed-lip expiration exercises. Both groups received selected intervention for 6 weeks, 5 days in a week, 2 times in a day, and 20 minutes per session. Pre and post-test measures of forced expiratory flow rate were taken by peak expiratory flow meter and chest expansion was measured by inch tape. Data were analysed using Statistical Package for Social Sciences (SPSS) version 17.0 software. The analysis was performed by using students paired t-test.Results: The study shows statistically significant improvement in diaphragmatic breathing exercise group when compared to pursed-lip expiration exercise group. The value of chest expansion has shown 2.04 % improvement in group1 and 1.01 % in group 2 whereas peak expiratory flow rate (PEFR) showed 16.9 % improvement in group 1 and 2.27 % in group 2.Conclusion: Diaphragmatic breathing exercises play a vital role in rehabilitation of asthmatic patients to gain functional improvement and independence.